We have to calculate sin x + sqrt ( 1 - (sin x)^2)

sin x + sqrt ( 1 - (sin x)^2)

=> sin x + sqrt ((cos x)^2)

=> sin x + cos x

This sum can be changed to many other forms but the basic result is sin x + cos x

**Therefore the sum = sin x + cos x**

To calculate the expression we'll have to transform the sum into a product. The terms of the su are not like trigonometric functions.

We'll re-write the second term: sqrt(1-sin^2x) = sqrt (cos x)^2

sin x + sqrt(1-sin^2x) = sin x + sqrt (cos x)^2

**sin x + sqrt(1-sin^2x) = sin x + cos x**

We'll express the function cosine, depending on the function sine.

cos x= sin (90-x)

The expression will become:

sin x + cos x = sinx + sin (90-x)

Now we can transform the expression into a product:

sin x + cos x = 2 sin (x+90-x)/2*cos (x-90+x)/2

sin x + cos x = 2 sin 45*cos [-(90-2x)/2]

sin x + cos x = 2* (sqrt2/2)*cos (45-x)

** sin x + cos x = sqrt 2*(cos 45*cos x + sin 45*sin x)**